The German-Jewish Experience Revisited - Aschheim, Steven E.; Liska, Vivian (De Gruyter, 2015)
This volume includes both historical treatments of differing German-Jewish understandings of their experience - their relations to their Judaism, general culture and to other Jews - and contemporary reflections and competing interpretations as to how to understand the overall experience of German Jewry.
Description based on print version record.
Kollektion FID Jüdische Studien / Collection FID Jewish Studies
Keywords: Social Science / Jewish Studies; Social sciences; Electronic books